2019
DOI: 10.1371/journal.pone.0211004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of localized vibration on alveolar bone of osteoporotic rats

Abstract: ObjectivesVibration, in the form of high frequency acceleration (HFA), stimulates alveolar bone formation under physiologic conditions and during healing after dental extractions. It is not known if HFA has an anabolic effect on osteoporotic alveolar bone. Our objective is to determine if HFA has a regenerative effect on osteoporotic alveolar bone.Methods and materialsAdult female Sprague-Dawley rats were divided into five groups: 1) Ovariectomized Group (OVX), 2) Sham-OVX Group that received surgery without o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…In our present study, we chose a rat model induced by OVX to mimic postmenopausal women with alveolar high-turnover bone loss. These patients usually feature high bone resorption and bone formation processes [ 32 , 33 ]. Our 3-D bone microstructure modeling revealed many parameters, e.g., Tb.Th, BV/TV, BS, Tb.N, Tb.Pf, Tb.Sp, as well as SMI were significantly changed.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we chose a rat model induced by OVX to mimic postmenopausal women with alveolar high-turnover bone loss. These patients usually feature high bone resorption and bone formation processes [ 32 , 33 ]. Our 3-D bone microstructure modeling revealed many parameters, e.g., Tb.Th, BV/TV, BS, Tb.N, Tb.Pf, Tb.Sp, as well as SMI were significantly changed.…”
Section: Discussionmentioning
confidence: 99%
“…The important observation to report here is the new bone formation labial to the initially proclined lower incisors after using HFV without gingival graft to cover the gum recession labial to the affected lower incisor ( Figure 6 b). It has been reported before that HFV not only can accelerate tooth movement with clear aligners [ 10 , 11 , 12 ] but also it increase bone formation and density after orthodontic treatment and after extraction of teeth as well [ 12 , 13 , 14 , 15 , 16 ]. Previous reports have shown that the increased bone density effect of HFV is mediated through its upregulation of osteogenic transcription factors (RUNX2, Foxo1, Osterix and Wnt signaling factors) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported before that HFV not only can accelerate tooth movement with clear aligners [ 10 , 11 , 12 ] but also it increase bone formation and density after orthodontic treatment and after extraction of teeth as well [ 12 , 13 , 14 , 15 , 16 ]. Previous reports have shown that the increased bone density effect of HFV is mediated through its upregulation of osteogenic transcription factors (RUNX2, Foxo1, Osterix and Wnt signaling factors) [ 13 ]. The biological mechanism of accelerating tooth movement by HFV has been reported in detailed before [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations